The sensitive and intelligible in spanish visual poetry - Hermosilla Álvarez, M.ª Ángeles (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Although the Platonic tradition separated the visible from the intelligible (the only source of knowledge), in the work of hermeneutics these two dimensions are linked, as shown by the scholar of Reception Aesthetics W. Iser, whose postulates are based on phenomenological theory and in Gestalt. If this premise is inherent to any interpretation, it is much more evident in visual poetry, where the understanding of the poem is the result of seeing and reading the text. Analyzing a representative sample of this poetic modality, with its diverse typology, is the objective of this work.